2004
DOI: 10.2105/ajph.94.7.1200
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Harassment, Discrimination, and Physical Violence Among Young Gay and Bisexual Men

Abstract: Absent policies preventing anti-gay mistreatment, empowerment and community-building programs are needed for young gay/bisexual men to both create safe social settings and help them cope with the psychological effects of these events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
224
1
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(249 citation statements)
references
References 24 publications
12
224
1
12
Order By: Relevance
“…20,21 Dimensions of minority stress, including experiencing and internalizing stigma due to sexual orientation, have been shown to have significant associations with negative health outcomes among adult gay and bisexual men, [21][22][23][24] sexual minority youth, 25 and in particular among young males who have sex with men (YMSM). [26][27][28] High rates of depression, substance use, and HIV/AIDS among groups of adult gay men have also been theorized to arise from negative childhood or adolescent experiences associated with their emergent samesex identities in heterosexist environments. 29 In general, sexual minority adolescents report negative health disparities compared to heterosexual adolescents due to increased risk of experiencing minority stress-related stressors, including bullying, verbal abuse, violence, and social marginalization.…”
mentioning
confidence: 99%
“…20,21 Dimensions of minority stress, including experiencing and internalizing stigma due to sexual orientation, have been shown to have significant associations with negative health outcomes among adult gay and bisexual men, [21][22][23][24] sexual minority youth, 25 and in particular among young males who have sex with men (YMSM). [26][27][28] High rates of depression, substance use, and HIV/AIDS among groups of adult gay men have also been theorized to arise from negative childhood or adolescent experiences associated with their emergent samesex identities in heterosexist environments. 29 In general, sexual minority adolescents report negative health disparities compared to heterosexual adolescents due to increased risk of experiencing minority stress-related stressors, including bullying, verbal abuse, violence, and social marginalization.…”
mentioning
confidence: 99%
“…Research indicates that lesbian, gay, and bisexual (LGB) individuals often experience additional stress that stems from prejudice and discrimination encountered in their daily lives, as compared to their heterosexual counterparts (Meyer, 2003; As emerging adults, YMSM may face increased conflict within their families as they begin to renegotiate/redefine these relationships. This conflict often results in physical or verbal victimization, particularly when they begin to disclose their sexual identity status (D'Augelli, 2005;Huebner, Rebchook, & Kegeles, 2004;Rivers, 2000;Willoughby, Malik, & Lindahl, 2006). A recent study found that LGB young adults (ages between 21 to 25) who experienced greater family rejection not only have increased odds of suicide attempts and depression, but are also significantly more likely to use drugs and engage in unprotected sexual intercourse (Ryan, Huebner, Diaz, & Sanchez, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…11 There is also growing evidence suggesting that HIV-positive individuals from traditionally stigmatized groups report higher rates of violence exposure and suicidal ideation. 12,13 Female sex workers in India are a traditionally stigmatized group, with high prevalence of HIV 10 and levels of stigma and violence that relate to the context of their work. 14 Yet, despite substantial investigation of their reproductive and sexual health needs, there is virtually no information on suicide and its determinants among female sex workers from low-and middle-income countries.…”
mentioning
confidence: 99%